Diagnostic Impact of Peritoneal Fluid Cytology in the Setting of Pediatric Uterine Adnexal Biopsy or Resection. (September 2016) - Vadva, Zareen; Laufer, Marc R.; Weldon, Christopher B.; Frazier, A. Lindsay; Vargas, Sara O.
Peritoneal fluid sampling has been recommended during surgery to resect an ovarian or fallopian tube mass, particularly for its staging relevance in ovarian carcinoma. Guidelines specifically for children are not well established, partly because of incomplete knowledge of the test characteristics in this age group. We sought to determine whether peritoneal fluid cytology sampling aids in diagnosis or staging of pediatric uterine adnexal masses. Children who underwent adnexal mass biopsy or excision from 1993 to 2014 were identified via archival review. Accompanying peritoneal fluid (washings or ascites) was assessed to determine whether it provided information beyond that in the accompanying surgical pathology specimen. Of 656 patients who underwent adnexal mass resection, 350 had concurrent cytologic sampling of peritoneal fluid. Median age at surgery was 14 years. Adnexal mass histologic examination showed tumors with malignant potential in 54 (8%) patients. Malignancy was identified in 3 cytology specimens (2 dysgerminomas and 1 mixed germ cell tumor). By today's guidelines, the malignant cytology specimens would have upstaged 1 of the 3 patients, and her therapy may not have changed. Cytology findings did not refine the histologic diagnosis in any benign or malignant case. Our findings demonstrated a low rate of malignancy (<1%) in peritoneal washing/ascites samples accompanying resection of a pediatric adnexal mass. Influencing staging or treatment by cytology sampling was rare in our cohort. Our findings provided benchmark data in an area dominated by adult studies. Furthermore, they may guide recommendations for cytologic fluid collection and processing tailored for pediatric populations.